2020
DOI: 10.1039/d0qm00157k
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated molecules for colourimetric and fluorimetric sensing of sodium and potassium

Abstract: New alkali metal ion sensors showing ratiometric colourimetric and fluorimetric responses with high selectivity and low limits of detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…Dual fluoroand chromoionophores have also been synthesized according to a similar method with both M−Na + and M−K + . 168 The authors demonstrated both ratiometric and fluorimetric sensing of both Na + and K + alongside the well-reported ionochromic response. Utilizing the tunability of the optoelectronic properties of conjugated materials, the authors demonstrate a bimolecular Na + /K + sensing system with a discrete colorimetric response to Na + or K + or both in solution.…”
Section: Ion-selective Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dual fluoroand chromoionophores have also been synthesized according to a similar method with both M−Na + and M−K + . 168 The authors demonstrated both ratiometric and fluorimetric sensing of both Na + and K + alongside the well-reported ionochromic response. Utilizing the tunability of the optoelectronic properties of conjugated materials, the authors demonstrate a bimolecular Na + /K + sensing system with a discrete colorimetric response to Na + or K + or both in solution.…”
Section: Ion-selective Interactionsmentioning
confidence: 99%
“…The molecules exhibit a low limit of detection across the visible spectrum. Dual fluoro- and chromoionophores have also been synthesized according to a similar method with both M–Na + and M–K + . The authors demonstrated both ratiometric and fluorimetric sensing of both Na + and K + alongside the well-reported ionochromic response.…”
Section: Ionic Interactions In Small-molecule Semiconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 When translated to a crown ether, analyte specificity may also be introduced; incorporation of 15-crown-5, a well-known sodium-chelating group, can impart the capacity for a selective sensing response to Na + , as previously recorded in analogous materials. 36,42,43 Synthetic route was also considered, and the Staudinger-Vilarrasa reaction 44 was selected as a suitable method, based on its prior success modifying EDOT to make electropolymerizable monomers in good yield 30 and the corresponding formation of an amide: a rigid and polar group which may aid adhesion to ITO, as has been demonstrated with other hydrogen-bonding carbonyl groups. 18…”
Section: Monomer Designmentioning
confidence: 99%
“…Researcher devoted more efforts for the recognition of sodium (Na + ) using crown ethers motif such as SBFI (sodium‐binding benzofuran isophthalate), [15] sodium green, [16] two photon excited probe, [17–19] crown ether‐appended boron dipyrrin, [20] ratiometric optical probes, [21,22] PET based optical probes, [23–25] calix[4] arene derivative bearing pyrene and perylene, [26] squaraine compound [27] sensors based on enzymes [28] . Several fluorescent based probes have been developed for sodium ions [29–31] . However, they were based on crown ether derived chelators, peptides, enzymes, proteins, and nucleic acids.…”
Section: Introductionmentioning
confidence: 99%